Capital Labour Substitution in the Large-scale Food-processing Industry in Pakistan: Some Recent Evidence (The Pakistan Development Review, 1993)
Food-processing is one of the first industries developed by man. Most agricultural commodities require some sort of processing for them to be edible. In primitive societies man processed his own food using the simple mortar and pestle. With the advent of industrialisation there emerged important implications for foodprocessing technologies. The workers in the industrial and cOlllDlercial sectors of urban areas required greater supplies of food. This encouraged the establishment of processing plants supplemented by storage facilities to ensure that the urban population received the food that they required. Food-processing, therefore, began to occupy a fairly predominant position in the overall industrial sector. Its , importance was heightened by its strong backward and forward linkages with the rest of the economy. In a labour-surplus developing economy, where most of the labour is unemployed or underemployed, the absorption of this surplus labour force in the industrial sector is an important issue. In recent decades, there has been significant growth in the industrial sector in most developing countries, in terms of both investment and output. This has not resulted in a similar rate of increase in labour absorption. This is often attributed to the adoption of inappropriate technologies see, for example, Malik and Battese (1986) or to the lack of technological alternatives. In this paper we seek to determine whether capital-labour substitution is possible in the large-scale food-processing sector in Pakistan.